Glucocorticoid-Induced Osteoporosis: Why Kids Are Different - Ward, Leanne M. (Frontiers in Endocrinology, 2020)
Glucocorticoids (GC) are an important risk factor for bone fragility in children with serious illnesses, largely due to their direct adverse effects on skeletal metabolism. To better appreciate the natural history of fractures in this setting, over a decade ago the Canadian STeroid-associated Osteoporosis in the Pediatric Population (“STOPP”) Consortium launched a six-year, multi-centre observational cohort study in GC-treated children. This study unveiled numerous key clinical-biological principles about GC-induced osteoporosis (GIO), many of which are unique to the growing skeleton. This was important, because most GIO recommendations to date have been guided by adult studies, and therefore do not acknowledge the pediatric-specific principles that inform monitoring, diagnosis and treatment strategies in the young. Some of the most informative observations from the STOPP study were that vertebral fractures are the hallmark of pediatric GIO, they occur early in the GC treatment course, and they are frequently asymptomatic (thereby undetected in the absence of routine monitoring). At the same time, some children have the unique, growth-mediated ability to restore normal vertebral body dimensions following vertebral fractures. This is an important index of recovery, since spontaneous vertebral body reshaping may preclude the need for osteoporosis therapy. Furthermore, we now better understand that children with poor growth, older children with less residual growth potential, and children with ongoing bone health threats have less potential for vertebral body reshaping following spine fractures, which can result in permanent vertebral deformity if treatment is not initiated in a timely fashion. Therefore, pediatric GIO management is now predicated upon early identification of vertebral fractures in those at risk, and timely intervention when there is limited potential for spontaneous recovery. A single, low-trauma long bone fracture can also signal an osteoporotic event, and a need for treatment. Intravenous bisphosphonates are currently the recommended therapy for pediatric GC-induced bone fragility, typically prescribed to children with limited potential for medication-unassisted recovery. It is recognized, however, that even early identification of bone fragility, combined with timely introduction of intravenous bisphosphonate therapy, may not completely rescue the osteoporosis in those with the most aggressive forms, opening the door to novel strategies.